Penerapan Media Explosion Box dalam Meningkatkan Keaktifan Siswa Kelas XI IPS 1 Pada Pelajaran Sosiologi di SMA N 6 Padang - Nabilla, Farah; Nora, Desri (Naradidik: Journal of Education and Pedagogy, 2022)
This research is motivated by the low activity of students in learning sociology at SMAN 6 Padang, especially in class XI IPS 1. The right effort to increase student activity in learning sociology in class XI IPS 1 is to apply explosion box media. The purpose of this study was to analyze how the application of the explosion box in increasing the activity of class XI IPS 1 student. This research method used classroom action research with a research sample of 39 students. Data collection techniques used are observation, interviews and documentation with research instruments, namely observation sheets and interview guidelines with quantitative descriptive analysis techniques. The theory used by researchers in this study is the behavioristic theory according to Thorndike. The results of this study prove that the application of explosion boxes can increase the activity of class XI IPS 1 SMA N 6 Padang students in the 2021/2022 academic year with the percentage before using the explosion box is 28.2% then after using the explosion box media it increases in cycle 1 50.6%, then in the second cycle increased to 74.0%. Learning using explosion box media can increase student activity because it involves students as a whole and makes students creative and active in receiving learning. So it can be concluded that the explosion box media is suitable for increasing the activity of class XI IPS 1 SMAN 6 Padang students.